The C. savignyi genetic map and its integration with the reference sequence facilitates insights into chordate genome evolution - Hill, Matthew M.; Broman, Karl W.; Stupka, Elia; Smith, William C.; Jiang, Di; Sidow, Arend (Genome Research, 2008)
The urochordate Ciona savignyi is an emerging model organism for the study of chordate evolution, development, and gene regulation. The extreme level of polymorphism in its population has inspired novel approaches in genome assembly, which we here continue to develop. Specifically, we present the reconstruction of all of C. savignyi’s chromosomes via the development of a comprehensive genetic map, without a physical map intermediate. The resulting genetic map is complete, having one linkage group for each one of the 14 chromosomes. Eighty-three percent of the reference genome sequence is covered. The chromosomal reconstruction allowed us to investigate the evolution of genome structure in highly polymorphic species, by comparing the genome of C. savignyi to its divergent sister species, Ciona intestinalis. Both genomes have been extensively reshaped by intrachromosomal rearrangements. Interchromosomal changes have been extremely rare. This is in striking contrast to what has been observed in vertebrates, where interchromosomal events are commonplace. These results, when considered in light of the neutral theory, suggest fundamentally different modes of evolution of animal species with large versus small population sizes.